Association of Lumbar Degenerative Disease and Revision Rate following Total Knee Arthroplasty - Malahias, Michael-Alexander; Gu, Alex; Richardson, Shawn S.; De Martino, Ivan; Mayman, David J.; Sculco, Thomas P.; Sculco, Peter K. (The Journal of Knee Surgery, 2020)
Recently, a variety of studies have analyzed the potential correlation between lumbar degenerative disease (LDD) and inferior clinical outcomes after total hip arthroplasty. However, there has been limited data concerning the role of LDD as a risk factor for failure after total knee arthroplasty (TKA). The aim of our study was to determine: (1) what is the association of LDDs with TKA failure (all-cause revision) within 2 years of index arthroplasty and (2) if patients with LDD and lumbar fusion are at increased risk of TKA revision within 2 years compared with LDD patients without fusion. Data were collected from the Humana insurance database using the PearlDiver database from 2007 to 2017. To assess aim 1, patients were stratified into two groups based on a prior history of LDD (International Classification of Diseases [ICD]-9 or -10 diagnostic codes). To analyze aim 2, patients within the LDD cohort were stratified based on the presence of lumbar fusion (lumbar fusion Current Procedural Terminology code). All-cause revision rate was 3.4% among LDD patients versus 2.4% of patients with non-LDD (p < 0.001) at 2 years. Following multivariate analysis, LDD patients were at increased risk of all-cause revision surgery at 2 years (odds ratio [OR]: 1.361; 95% confidence interval [CI]: 1.238–1.498; p < 0.001) as well as aseptic loosening (OR: 1.533; 95% CI: 1.328–1.768; p < 0.001), periprosthetic joint infection (OR: 1.245; 95% CI: 1.129–1.373; p < 0.001), and periprosthetic fracture (OR: 1.521; 95% CI: 1.229–1.884; p < 0.001). Among LDD patients, patients who have a lumbar fusion had an all-cause revision rate of 5.0%, compared with 3.2% among LDD with no lumbar fusion patients at 2 years (p = 0.021). Following multivariate analysis, lumbar fusion patients were at increased risk of all-cause revision surgery (OR: 1.402; 95% CI: 1.362–1.445; p = 0.028), aseptic loosening (OR: 1.432; 95% CI: 1.376–1.489; p = 0.042), and periprosthetic fracture (OR: 1.302; 95% CI: 1.218–1.392; p = 0.037). Based on these findings, TKA candidates with preoperative LDD should be counseled that TKA outcome may be impaired by the coexistence of lumbar spine degenerative disease. This is Level III therapeutic study.
Keywords: total knee arthroplasty; lumbar degenerative disease; lumbar fusion